John Milton: Paradise lost - Edwards, Mike 1942- (Analysing Texts, 2013)
This essential volume helps students to appreciate Milton's classic work. Part I uses carefully selected extracts for close textual analysis, while Part II examines the historical and literary contexts and key criticism. The volume is an ideal introductory guide for those who are studying 'Paradise Lost' for the first time